Prevalence and predictors of hand involvement in Thai patients with systemic sclerosis - Suparaporn Wangkaew (2018)
© 2016 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Aim: Data regarding the clinical and radiographic hand involvement in Asian patients with systemic sclerosis (SSc) are limited. Thus, we determined the prevalence of clinical and radiographic hand involvement in Thai SSc patients, comparing diffuse cutaneous SSc (dcSSc) and limited cutaneous SSc (lcSSc). We also determined the factors associated with arthritis, contracture of fingers and digital ulcers. Method: SSc patients seen at the Rheumatology Clinic, Chiang Mai University, Thailand, from December 2012 to June 2013 were consecutively invited to enroll in the study. After study entry, demographic data, clinical features and hand radiographs were evaluated. Result: We studied 110 SSc patients (73 dcSSc) with mean ± SD age of 53.2 ± 9.2 years and disease duration from non-Raynaud's phenomenon of 4.9 ± 4.8 years. The prevalence of arthritis, finger contractures and digital ulcers were 10 (9.1%), 47 (42.7%), and 14 (12.7%), respectively. DcSSc patients had significantly more of the following hand complications than lcSSc patients: digital pitting scar (53.4% vs. 27.0%, P = 0.008), digital ulcer (17.8% vs. 2.7%, P = 0.032), traumatic ulcer (27.4% vs. 0%, P < 0.001), acrolysis (45.2% vs. 18.9%, P = 0.007) and flexion contracture (60.3% vs. 8.1%, P < 0.001). Radiographic finger contractures were more prevalent in the dcSSc subset. In multivariate logistic regression analysis, a positive rheumatoid factor was associated with arthritis; dcSSc, arthritis and modified Rodnan skin score (MRSS) > 18 were associated with contracture of fingers. Furthermore, hand MRSS > 4 was associated with digital ulcers. Conclusion: Our results confirm that dcSSc patients had more severe clinical hand complications than lcSSc. However, radiographic findings were similar among subgroups, except that more finger contractures were seen in dcSSc. Finally, the presence of rheumatoid factor is associated with arthritis, and high MRSS is associated with finger contractures and digital ulcers.